2012
DOI: 10.1021/jp3002405
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Organic Solvent and Crystal Water on γ-Chymotrypsin in Acetonitrile Media: Observations from Molecular Dynamics Simulation and DFT Calculation

Abstract: The use of enzymes in nonaqueous solvent has been one of the most exciting facets of enzymology in recent times; however, the mechanism of how organic solvent and essential water influence on structure and function of enzyme has been not satisfactorily explained in experiments, which limit its further application. Herein, we used molecular dynamics (MD) simulation to study γ-chymotrypsin in two types of media (viz., acetonitrile media with inclusion of 151 crystal water molecules and aqueous solution). On the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 90 publications
4
16
0
Order By: Relevance
“…The observation implies that the adsorption of CNT would not significantly influence the specificity of α-ChT in aqueous solution. However, the S1 pocket of the free enzyme in heptane solvent is almost fully closed and distinctly different from those in aqueous solution, implying a change in the specificity of the enzyme, consistent with the experiment finding 38 49 . In contrast, the shape of the S1 pocket for the immobilized enzyme in heptane solvent still presents relative “open” state, similar to those in aqueous solution.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The observation implies that the adsorption of CNT would not significantly influence the specificity of α-ChT in aqueous solution. However, the S1 pocket of the free enzyme in heptane solvent is almost fully closed and distinctly different from those in aqueous solution, implying a change in the specificity of the enzyme, consistent with the experiment finding 38 49 . In contrast, the shape of the S1 pocket for the immobilized enzyme in heptane solvent still presents relative “open” state, similar to those in aqueous solution.…”
Section: Resultssupporting
confidence: 88%
“…Heptane was chosen in this work since it is one of the most common nonpolar organic media for non-aqueous enzymatic catalysis 35 36 . In previous work 37 38 , we already used MD simulation to study the effects of the organic solvent and water content on the structure and function of the chymotrypsin. In the work, we further revealed the molecular mechanism concerning the effect of the immobilization of CNT on its structure and stability in the non-polar heptane media, in order to provide valuable information for improving its catalytic properties and advancing its application in non-aqueous media.…”
mentioning
confidence: 99%
“…Similar phenomena were observed in organic solvents with C=O (e.g., acetone and N,N-dimethylformamide), C"N (e.g., acetonitrile), and cyclic molecules (e.g., benzene, dioxane and tetrahydrofuran) as in alcohols [37,38]. Through MD simulation, acetonitrile molecules were found to penetrate into the active site of lipase, leading to structure variation of the active site and therefore the drop in the enzymatic activity in acetonitrile aqueous solution [38]; acetone, acetonitrile, and 1,4-dioxane could bind to the active site of subtilis and disturb its structure [21,34].…”
Section: Effect Of the Functional Groups Of Organic Solventsupporting
confidence: 60%
“…Through MD simulation, acetonitrile molecules were found to penetrate into the active site of lipase, leading to structure variation of the active site and therefore the drop in the enzymatic activity in acetonitrile aqueous solution [38]; acetone, acetonitrile, and 1,4-dioxane could bind to the active site of subtilis and disturb its structure [21,34]. Gupta et al [39] observed that the activity of polyphenol oxidase and trypsin reduced to different extents by 50% of tetrahydrofuran, dioxane, acetone, and acetonitrile.…”
Section: Effect Of the Functional Groups Of Organic Solventmentioning
confidence: 99%
“…Molecular dynamics (MD) simulations have been used successfully to study the structure and function of proteins to obtain microscopic information at the molecular level and to supplement experimental investigations [18][19][20][21][22], including study of GPCRs [23,24]. Previous MD studies on GPCRs have focused largely on the effects of ligand binding.…”
Section: Introductionmentioning
confidence: 99%